A multitower measurement network estimate of California's methane emissions. Issue 19 (3rd October 2013) - Jeong, Seongeun; Hsu, Ying‐Kuang; Andrews, Arlyn E.; Bianco, Laura; Vaca, Patrick; Wilczak, James M.; Fischer, Marc L.
Abstract [1] We present an analysis of methane (CH4) emissions using atmospheric observations from five sites in California's Central Valley across different seasons (September 2010 to June 2011). CH4 emissions for spatial regions and source sectors are estimated by comparing measured CH4 mixing ratios with transport model (Weather Research and Forecasting and Stochastic Time‐Inverted Lagrangian Transport) predictions based on two 0.1° CH4 (seasonally varying "California‐specific" (California Greenhouse Gas Emission Measurements, CALGEM) and a static global (Emission Database for Global Atmospheric Research, release version 42, EDGAR42)) prior emission models. Region‐specific Bayesian analyses indicate that for California's Central Valley, the CALGEM‐ and EDGAR42‐based inversions provide consistent annual total CH4 emissions (32.87 ± 2.09 versus 31.60 ± 2.17 Tg CO2eq yr−1; 68% confidence interval (CI), assuming uncorrelated errors between regions). Summing across all regions of California, optimized CH4 emissions are only marginally consistent between CALGEM‐ and EDGAR42‐based inversions (48.35 ± 6.47 versus 64.97 ± 11.85 Tg CO2eq), because emissions from coastal urban regions (where landfill and natural gas emissions are much higher in EDGAR than CALGEM) are not strongly constrained by the measurements. Combining our results with those from a recent study of the South Coast Air Basin narrows the range of estimates to 43–57 Tg CO2eq yr−1 (1.3–1.8 times higher than the current state inventory). These results suggest that the combination of rural and urban measurements will be necessary to verify future changes in California's total CH4 emissions.